Adoption of Minimally Invasive Surgery and Decrease in Surgical Morbidity for Endometrial Cancer Treatment in the United States. Issue 2 (February 2018) - Casarin, Jvan; Multinu, Francesco; Ubl, Daniel S.; Dowdy, Sean C.; Cliby, William A.; Glaser, Gretchen E.; Butler, Kristina A.; Ghezzi, Fabio; Habermann, Elizabeth B.; Mariani, Andrea
Abstract : OBJECTIVE: To assess how the widespread adoption of minimally invasive surgery in the United States is associated with changes in 30-day morbidity and mortality in endometrial cancer treatment. METHODS: In this retrospective cohort study, the American College of Surgeons' National Surgical Quality Improvement Project database for 2008–2014 was reviewed for patients who had undergone surgery for endometrial cancer according to their primary Current Procedural Terminology (CPT) codes. Women with CPT codes for advanced cancer or with disseminated disease were excluded. A trend analysis across the time period by surgical approach (open surgery through laparotomy, vaginal surgery, and minimally invasive surgery) was performed using a Cochran-Armitage test for trend. Thirty-day surgical outcomes were compared between patients who had minimally invasive surgery and open surgery. Inverse probability of treatment weighting models were used to investigate the independent effect of minimally invasive surgery on 30-day outcomes. RESULTS: Overall, 12, 283 patients met the inclusion criteria. A significant implementation of minimally invasive surgery (24.2–71.4%) and a concomitant decrease in open surgery through laparotomy (71.1–26.4%) were observed from 2008 to 2014 (both P <.001). Rate of vaginal surgery did not change over time (1.5–2.2%, P =.06). After adjusting for possible confounders, open surgery (compared with minimally invasive surgery) was independently associated with increased odds of major complications (n=347 versus n=274, adjusted odds ratio [OR] 2.4, 95% CI 2.0–2.8), readmission (n=269 versus n=238, adjusted OR 2.2, 95% CI 1.8–2.6), reoperation (n=80 versus n=93, adjusted OR 1.5, 95% CI 1.2–2.1), superficial surgical site infection (n=190 versus n=55, adjusted OR 6.8, 95% CI 5.0–9.2), perioperative transfusion (n=430 versus n=149, adjusted OR 5.9, 95% CI 4.8–7.1), and death (n=41 vs, n=20, adjusted OR 3.8, 95% CI 2.2–6.6). A comprehensive decrease in 30-day morbidity for the treatment of endometrial cancer overall was observed from 2008 to 2014 ( P <.001), whereas 30-day mortality remained stable ( P =.24). CONCLUSION: The widespread adoption of minimally invasive surgery is associated with substantial decreases in 30-day morbidity, readmission, and reoperation for women treated for endometrial cancer in the United States. Abstract : The adoption of minimally invasive surgery is associated with a reduction of 30-day morbidity, readmissions, and reoperations for endometrial cancer treatment in the United States.